1989
DOI: 10.2307/3801137
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction in Black Bears in the Southern Appalachian Mountains

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
64
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(68 citation statements)
references
References 9 publications
4
64
0
Order By: Relevance
“…Mating occurs from June through early August, peaking in early July (Eiler et al 1989). Implantation of the blastocyst (i.e.…”
Section: E Reproductionmentioning
confidence: 99%
“…Mating occurs from June through early August, peaking in early July (Eiler et al 1989). Implantation of the blastocyst (i.e.…”
Section: E Reproductionmentioning
confidence: 99%
“…During good natural food years transition from subadult to breeding adult was assumed to occur on average at age 4 such that bears typically would give birth to their first litter at age 5 (Baruch-Mordo, 2012;Beston, 2011). We assumed a decrease in the transition rate from subadult to adult during poor food years, even though literature supporting this was sparse (Eiler et al, 1989). We also assumed a decrease in the transition rate of breeding adults to adult with cub(s) during poor natural food years as litter production depends on body condition (Noyce and Garshelis, 1994) and has been observed to decrease when natural foods are not available (Beck, 1991;Bridges et al, 2011;Rogers et al, 1976).…”
Section: Scenario Developmentmentioning
confidence: 99%
“…There was little information about vital rates calculated during good and poor natural food years in the literature; we thus parameterized the Baseline scenario vital rates such that the vital rate mean taken across good and bad years was near values calculated in a meta-analysis for Western black bears (Beston, 2011). We assumed that poor natural food production more negatively influenced younger stage class survival rates than adult survival (Eiler et al, 1989;Schrage and Vaughan, 1995;Noyce and Garshelis, 1994;Kasbohm et al, 1996). During good natural food years transition from subadult to breeding adult was assumed to occur on average at age 4 such that bears typically would give birth to their first litter at age 5 (Baruch-Mordo, 2012;Beston, 2011).…”
Section: Scenario Developmentmentioning
confidence: 99%
“…Thus, it is important, especially for pregnant female bears, to accumulate body fat in autumn. It has been suggested that the amount of fat store might influence the implantation and fertility rates in bears [7]. Hence, their reproductive success is dependent upon maternal fat accumulation in autumn.…”
mentioning
confidence: 99%